Judges’ Ratio Decidendi to Accept and Reject Interfaith Marriage in The Perspective of Indonesian Positive Law - Elmira Qurrota A'yunina A'yunina; Syabbul Bachri (Jurnal Hukum Prasada, 2023)
The existence of interfaith marriages in Indonesia does not yet have regulations that clearly regulate its implementation. This causes differences in decisions given by judges in each case. Ratio decidendi is a reason or argument used by judges to give a decision in a case that is always based on applicable laws and regulations. In addition to the absence of regulations that regulate exactly the implementation of interfaith marriages, the difference of opinion given by the judges in decisions related to the implementation of interfaith marriages makes people even more confused about the legality of implementing interfaith marriages in Indonesia. The purpose of this study is to analyze the ratio decidendi of judges in each decision, whether from a decision to reject or grant a decision, as well as to analyze the perspective of Indonesian positive law regarding the implementation of interfaith marriages. This study uses a type of normative juridical research that uses a case approach and a comparative approach. The results of this study in general are that actually interfaith marriage cannot be justified in its implementation, because there are several laws that actually regulate marriages carried out by two people who have different religions and beliefs.